Bibliometric analysis of publications on genetic polymorphism and external apical root resorption research - Liz Helena Moraes PINHEIRO; Dalila Ferreira Silvano de MOURA; Leonardo Santos ANTUNES; Lívia Azeredo Alves ANTUNES (Dental Press Editora, 2024)
ABSTRACT Objective: This study aimed to analyze the scientific production of genetic polymorphisms and external apical root resorption (EARR) to establish main findings, geographic trends, and research gaps for possible future investigations. Methods: Unrestricted publications were searched using the Scopus database (March 2023) to include studies that addressed the association between genetic polymorphisms and EARR. Case-control, cohort, cross-sectional, and review studies were considered eligible. The softwares VOS viewer™ and Bibliometrix were used for data analysis. Results: Of the 44 studies analyzed, "Iglesias-Linares A" was the most cited author. The University of Seville (Spain) conducted the most research on this topic. Brazil, Spain, and the USA were the leading countries in terms of citations. The most frequent term in the co-occurrence of keywords was "EARR." The journal American Journal of Orthodontics and Dentofacial Orthopedics presented a great relevance in the area, demonstrating a high number of publications. Several genetic polymorphisms have been investigated, with interleukins being the most studied. Conclusion: Endodontics is an area of research that should focus more on root resorption and genetic polymorphisms, as it still underexplored, compared to orthodontics. Polymorphisms have been studied as possible predictors of EARR caused by orthodontic tooth movement. However, the gap in the research indicates a need to search for new genes associated with EARR.